139k views
3 votes
If a+b=1, find N=a^3+b^3+3ab

2 Answers

2 votes

Answer:

1

Explanation:

Using the identity

a³ + b³ = (a + b)³ - 3ab(a + b), then

a³ + b³ + 3ab(a + b) = (a + b)³

a³ + b³ + 3ab(1) = 1³ , hence

a³ + b³ + 3ab = 1

User Jer K
by
5.7k points
2 votes

Answer: 1

Explanation:

a + b = 1

a³ + b³ = (a + b)(a² - ab + b²) formula for a perfect cube

a³ + b³ + 3ab = (a + b)(a² - ab + b²) + 3ab

= 1 (a² - ab + b²) + 3ab

= a² - ab + b² + 3ab

= a² + 2ab + b² this is a perfect square

= (a + b)(a + b)

↓ ↓

= (1) (1)

= 1

User Bryce Fischer
by
5.6k points